2020
DOI: 10.1161/strokeaha.120.029959
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Ischemic Stroke in Patients With Atrial Fibrillation After Extracranial Hemorrhage

Abstract: Background and Purpose: Anticoagulation therapy not only reduces the risk of ischemic stroke in atrial fibrillation (AF) but also predisposes patients to hemorrhagic complications. There is limited knowledge on the risk of first-ever ischemic stroke in patients with AF after extracranial hemorrhage (ECH). Methods: We conducted a retrospective study using the California State Inpatient Database including all nonfederal hospital admissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Despite its relatively low incidence, acute VBAO is the most dangerous type of cerebral vessel occlusion and can be caused by severe local atherosclerotic stenosis or distant embolization (4), with the former being more common (5). Without any specific treatment, the mortality rate of patients with acute ischemic stroke caused by VBAO is approximately 80-90% (6). Therefore, effective treatments for VBAO have attracted much attention globally.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its relatively low incidence, acute VBAO is the most dangerous type of cerebral vessel occlusion and can be caused by severe local atherosclerotic stenosis or distant embolization (4), with the former being more common (5). Without any specific treatment, the mortality rate of patients with acute ischemic stroke caused by VBAO is approximately 80-90% (6). Therefore, effective treatments for VBAO have attracted much attention globally.…”
Section: Introductionmentioning
confidence: 99%
“…AF is associated with an increased risk of intracranial hemorrhage, although this is largely related to concomitant anticoagulant therapy. In a limited number of cases, it has been shown that patients with atrial fibrillation can develop extracranial hemorrhage (ECH) [99]. However, it is unclear whether patients with AF may have a better or worse prognosis than those without arrhythmia [100].…”
Section: Individual Risk Factors In Patients With Hemorrhagic Transfo...mentioning
confidence: 99%
“…The bleeding risk is known as the main problem of all anticoagulant therapies, despite their proven effectiveness [99]. The introduction of direct oral anticoagulants (DOACs) into clinical practice means that major hemorrhages, especially intracranial, associated with therapy are certainly reduced; however, the risk of bleeding, even with these drugs, is not eliminated.…”
Section: Therapies and Treatments Influences In Patients With Hemorrh...mentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with a history of extracranial hemorrhage, studies have shown an increased risk of ischemic stroke. Thus, in these patients, anticoagulation should generally be resumed after the bleeding source is successfully treated 34 . On the other hand, left atrial appendage occlusion can be considered in patients with recurrent major extracranial hemorrhage or those whose bleeding source cannot be successfully treated such as those with multiple gastrointestinal arteriovenous malformations.…”
Section: Atrial Fibrillationmentioning
confidence: 99%